Impact of Educational Environment on Learners’ Engagement: Basis for Academic Achievement - Arocha, Radjay (International Journal of Innovative Research in Engineering & Multidisciplinary Physical Sciences, 2025)
The educational environment significantly influences learners’ development, particularly their social interactions, cognitive growth, and engagement in academic activities. A positive environment fosters collaboration, scaffolding within the Zone of Proximal Development (ZPD), and cultural responsiveness, all contributing to higher learner engagement. This study examined the impact of the educational environment on learners’ engagement to provide a basis for academic enhancement. A descriptive-correlational research design was employed. The study involved 235 teachers from Sapang Dalaga District, Division of Misamis Occidental. Data were collected using a researcher-made questionnaire measuring components of the educational environment and learner engagement. Analysis included arithmetic means for descriptive results and Pearson’s r for correlational analysis. Findings revealed a high extent of impact of the educational environment on learners, with mean scores for Social Interaction (3.459), ZPD (3.414), Scaffolding (3.412), and Cultural and Environmental Influence (3.450). Learners’ engagement was also rated high across Behavioral (3.480), Emotional (3.468), and Cognitive Engagement (3.524). However, the correlation analysis showed no statistically significant relationship between the educational environment and learners’ engagement (r = 0.007, p = 0.912). Despite high ratings for both the educational environment and learner engagement, no significant association was found, suggesting that learner engagement is influenced by multiple complex factors beyond the educational setting. Further research is needed to explore other variables affecting engagement to inform more effective academic interventions.